Development of indicators to measure health system capacity for quality abortion care in 10 countries: a rapid assessment of a measurement framework and indicators - Leopold Ouedraogo; Katy Footman; Fahdi Dkhimi; Bela Ganatra; Mohamed Ali; Antonella Lavelanet; Souleymane Zan; Shikha Bansal; Karima Gholbzouri; Eman Aly; Nilmini Hemachandra; Laurence Läser; et al. (BMJ Publishing Group, 2024)
Introduction A significant gap exists in the availability of indicators and tools to monitor health system capacity for quality abortion care at input and process levels. In this paper, we describe the process and results of developing and assessing indicators to monitor health system capacity strengthening for quality abortion care.Methods As part of a 4-year (2019-2022) multicountry project focused on preventing unsafe abortion using a health system strengthening approach in 10 countries, we developed a monitoring framework with indicators and metadata. Through an internal consultative process, we identified a structured list of operational health system capacity indicators for abortion. After implementing the indicators for baseline and annual project monitoring, project staff from 10 teams assessed each indicator using 4 criteria: validity, feasibility, usefulness and importance.Results We identified 30 indicators aligning with 5 of the 6 WHO health system building blocks (excluding service delivery): 6 indicators in leadership and governance, 5 in health workforce, 6 in health information, 8 in access to medicines and health products and 5 in health financing. In our assessment of indicators, average scores against the predetermined criteria were lowest for feasibility (7.7 out of 10) compared with importance (8.5), usefulness (8.9) and validity (9.3). Assessors highlighted the need for fewer and less complex indicators, simplified language, clearer benchmarks, for indicators to be abortion-specific, less subjective and for future frameworks to also include service delivery and research and innovation.Conclusion We used 30 indicators to monitor health system capacity for quality abortion care in 10 countries and gathered critical feedback that can be used to further strengthen the set of indicators in future work. Establishing core input and process indicators will be critical to inform and support evidence-based policy and programme improvements for quality abortion care.